MODEL PEMBELAJARAN KURIKULUM UNTUK ANAK USIA DINI DALAM PENDEKATAN BANK STREET APPROACH DAN HIGH SCOPE - Sudrajat, Iyus; Sawalianti, Asri; Uminah, Uminah; Noviyani, Lisa (Journal Education and Government Wiyata, 2024)
The development of science and technology in modern times has driven various changes. Technological advances require individuals to acquire more skills, both in knowledge, attitudes and behavior. The goal is for each individual to be able to face and adapt to changes, including in the field of education. Education is a necessity for all individuals to obtain quality education is a right for every citizen, including early childhood. Proper early childhood education also depends on quality learning and teachers. Therefore, parents need to know and understand how their children can learn well and have fun at school. So that children can explore and develop their potential. This research uses a literature study (library research) conducted by collecting library data and reading previous journals in this research. The purpose of this research is to find out the curriculum learning model for early childhood through the approach: bank street and high/scope, the learning model is a plan or model that describes the detailed process and the creation of environmental situations that allow children to interact during learning, so that changes and development occur in children. The learning model is taken from two syllables, namely: Model and Learning. Each of these words has a different meaning.